Recommended guidelines of electronic academic assets - Ibrahim, Subariah; Salleh, Mazleena (UTM, 2002)
As the country moves into the Information Age, government agencies including universities are revolutionizing the way they operate. Computer system has become a part of their staff office equipment and most of the information kept is in the electronic form. To make this information useful, it must be accessible when and where it is needed. Now the world trend is towards global interconnectedness and Internet connectivity makes it feasible for information to be available globally. However, managing electronic data as well as connectivity without employing any security measures and controls can result in the compromise, improper modification, or destruction of the information. Disclosure of sensitive information to the wrong hands can ruin and destroy businesses, corporate agency or government. This guideline provides security guidelines to academic staff in the university, and to others who are responsible for the security of electronic information in a university environment. The objective of this guideline is to address issues in the context of protecting electronic academic assets. It discusses some of the threats and vulnerabilities of these academic assets, and some of the security controls that can be employed to reduce the risks.